Micro-CT analysis of deviations in fiber orientation and composite stiffness near the microvascular channels embedded in glass-fiber reinforced composites. (1st April 2020) - Sabuncuoglu, Baris; Tanabi, Hamed; Soete, Jeroen; Lomov, Stepan V.
Abstract: Microvascular channels, embedded in fiber-reinforced composites are introduced as an efficient tool for internal damage monitoring, self-healing, and thermal management applications. As an adverse effect, vascular channels cause a disturbance in the fibers around the channel region. In this study, first, the fiber orientation around the channel is evaluated using micro-CT images analyzed with VoxTex software. Variation in the stiffness around the channels is determined using micro-homogenization. The results revealed orientation disturbance in the out-of-plane direction with a maximum of about 6°. The micro-channel affected the nearby local stiffness as well, reducing it by up to 19%.